2021
DOI: 10.21608/esjp.2021.233540
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of root rot, wilt diseases complex in offshoot date palm and improvement of growth parameters in New Valley Governorate, Egypt

Abstract: Root Rot wilt disease complex were detected in different date palm offshoots in nurseries and new orchards in New Valley Governorate. Pathogenicity tests showed that Fusarium oxysporum, F. solani and F. moniliforme were pathogenic to date palm offshoots (. Saidy) but they differed in their pathogenic capabilities. The effect of Bacillus subtilis (BSM1), B. megaterium (BMM5), B. cereus (BCM8), Trichoderma viride (TVM2), T. harzianum (THM4) as bioagents against root rot/ wilt disease complex of date palm offshoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In addition, our results are in harmony with those reported by El-Morsi et al (2021) who isolated F. solani, F. oxysporum, F. equiseti, F. moniliforme and F. Semitectium from date palm offshoots showing root rot symptoms and their pathogenicity was confirmed on cv. Saidy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our results are in harmony with those reported by El-Morsi et al (2021) who isolated F. solani, F. oxysporum, F. equiseti, F. moniliforme and F. Semitectium from date palm offshoots showing root rot symptoms and their pathogenicity was confirmed on cv. Saidy.…”
Section: Discussionsupporting
confidence: 92%
“…However, under greenhouse conditions Uniform 39 % SE, Tshgarin 30 % SL and Hexaten gave the highest efficacy for controlling date palm root rot on the two cultivars during the two seasons, while the lowest efficacy was recorded when seedlings were treated with T34 and Serenade ASO 1.34% SC, respectively. El-Morsi et al, (2021) Studies the antagonistic effects of some Bacillus and Trichoderma species as bio control agents against root rot of date palm offshoots in El-Dakhla and El-Kharga under natural infection in nursery. The results show significant reduced severity compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that biological control agents such as AMF and BY caused higher reduction in root rot and wilt severity in many crops (Azcon -Aguilar and Barea , 1996, El-Tarabily and Sivasithamparam, 2006and El-Morsi et al, 2015. Arras (1996) stated that antibioses, competition for colonization sites and nutrients and degradation of the pathogen toxins and enzymes by yeasts may be involved in the suppuration of the growth of different patho genic fungi in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 77%